Third Five Year Plan of Chitradurga District Government of Mysore - Planning Commission (Planning Commission, 1965)
Chitra Durga is one of the five Districts of the Bangalore Division, and consists of nine taluka. For purposes of administrative convenience, the District is divided into two sub-divisions, viz., (1) Chitra Durga Sub-Division comprising Chitra Durga, Haripur, Chalker and Molakalmuru taluks and (2) Davangere Sub-Division, comprising Davangere, Harihar, Jagahir, Holalkere and Ilosadurga taluka.
Planning, Housing and Social Welfare Department Government of Mysore